Social Media Marketing and Educational Institution Brand Awareness, Image, and Attitude - Carolin Marhareita; Iwan Waani Kila; Deske W. Mandagi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This empirical study seeks to elucidate the impact of social media marketing (SMM) on forming brand awareness, brand image, and brand attitude within the educational institution context. In pursuit of these objectives, data were collected through a survey involving 149 respondents comprising current university students and graduates in North Sulawesi. The analysis was conducted utilizing Structural Equation Modelling (SEM) with SmartPLS. The study's results disclose significant and positive relationships between SMM and brand attitude, brand awareness, and brand image. Furthermore, it was found that brand image significantly influences brand attitude, while brand awareness plays a pivotal role in shaping the brand image. However, it was observed that brand awareness did not exhibit a significant positive effect on brand attitude. These findings offer valuable insights for educational administrators, underscoring the central role of social media in fortifying institutional branding. By comprehending the intricate interplay of these variables, institutions can strategically harness social media platforms to augment brand awareness, cultivate a positive brand image, and ultimately foster a favorable brand attitude. This understanding is critical for their marketing and branding efforts within an increasingly digital and globalized educational landscape.